ANALISIS MINAT ORANG TUA DALAM MEMILIH LEMBAGA PESANTREN DI MTS KUN KARIMA PANDEGLANG - Taufik Hidayat; Wasehudin Wasehudin; M. Nur Arifin; Eneng Muslihah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2025)
Kun Karima Islamic Boarding School in Pandeglang, as one of the Islamic educational institutions in Pandeglang Regency, plays a vital role in shaping the character and knowledge of its students. The success of personality education is strongly influenced by the internalization of religious values within the learners. This study employs a qualitative method with a descriptive approach to illustrate the alignment between parental attention, student interest, and the duration of learning in developing Islamic character. The findings reveal that parents’ interest in choosing MTs Kun Karima Pandeglang as a pesantren-based educational institution is influenced by the need for an education system capable of comprehensively shaping students’ Islamic character. Parents perceive the pesantren system as more effective in integrating Islamic Religious Education with daily life practices through the habituation of worship, teacher role modeling, a religious environment, and an evaluation system that emphasizes not only academic achievement but also the cultivation of morality and religious behavior. Pesantren is considered able to balance mastery of knowledge with the strengthening of spiritual values, thereby producing graduates who are not only intellectually competent but also possess faith, piety, and noble character as essential provisions for facing the challenges of modern life.